Places of silence, journeys of freedom : the fiction of Paule Marshall - DeLamotte, Eugenia C. (Philadelphia : University of Pennsylvania Press, 1998)
Places of Silence, Journeys of Freedom is the first study of Paule Marshall's work to focus explicitly on her contribution to feminism. It is also the first to identify one of her original contributions to narrative art - a technique of "superimposition" or "double exposure" through which her books have explored topics now at the heart of feminist debate
"The mother's voice" -- Losses and recognitions: allegorical realism in The chosen place, the timeless people -- Voice, spirit, materiality, and the road to freedom: third world feminism in Praisesong for the widow -- Daughters: conflations of discourse.
Includes bibliographical references (pages 187-194) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Marshall, Paule, -- 1929-2019 -- Criticism and interpretation; Marshall, Paule, -- 1929-2019; Marshall, Paule -- 1929-2019; Marshall, Paule, -- 1929-; Marshall, Paule; Women and literature -- United States -- History -- 20th century; Caribbean Americans -- Intellectual life; Caribbean Area -- In literature; African Americans in literature; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Américains d'origine antillaise -- Vie intellectuelle; Caraïbes (Région) -- Dans la littérature.; Noirs américains dans la littérature.; African Americans in literature; Literature; Women and literature; Caribbean Area; United States; Erzähltechnik; Feminismus; Roman; 1900-1999; African Americans in literature; Caribbean Americans -- Intellectual life; Caribbean Area -- In literature; Marshall, Paule -- 1929- -- Criticism and interpretation; Women and literature -- United States -- History -- 20th century; Criticism, interpretation, etc; History